Description of the experimental setup for investigation of the movement of foam in a horizontal cylindrical channel - Parmon Валерий; Kamlyuk Андрей; Grachulin Александр; Korsakov Максим; Navrotskiy Олег (Vestnik of the Institute for Command Engineers of the MES of the Republic of Belarus, 2015)
The authors propose the experimental setup for investigation of the movement of water and foam in the hose line of compressed air foam system. Describes the principle of operation of the setup. Experimentally determined pressure drop when water moves in the hose line. Compared the experimental results with the calculated values.